3D dynamical structuring of a high latitude erupting prominence: II- Analysis of the coronal context and eruption. Issue Volume 8:Issue S300(2013) (6th January 2014) - Koutchmy, Serge; Filippov, Boris; Tavabi, Ehsan; Bazin, Cyrille; Weiller, Sylvain
Abstract: Both the origin of the quiescent prominences and their eruption related to CMEs event are still a matter of extended studies. The case of high latitudes quiescent prominences producing slow CMEs can be considered as a potential component of the slow wind. A high latitude prominence was observed on November 13 - 14, 2011. A schematic representation of flux rope is proposed to describe the magnetic structure of the prominence prior to its eruption.